Islam in Malaysian foreign policy - Nair, Shanti (Politics in Asia series., 1997)
A case study of a multi-ethnic Muslim state and a contribution to the study of the domestic functions of foreign policy. The book also addresses the real and imagined significance of Islam as a force in contemporary global politics.